Reassessing the role of interpersonal trust in organizational settings. - Dirks, K. T. (Institutional Knowledge at Singapore Management University, 1998)
Most of the research on trust rests on, or is intended to examine, the following proposition: interpersonal trust exerts positive effects on interpersonal behavior and work group performance. We examine the proposition's validity by reviewing existing research. Finding limited support, we present several alternative roles fortrust in organizational settings.